A COMPARATIVE STUDY ON CUSTOMER LOYALTY BETWEEN AIRTEL AND JIO CONSUMERS - Devi, S. Kalpana (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Customer loyalty is a critical driver of success in the highly competitive telecommunications industry, where brands continuously vie for consumer attention and retention. This study explores and compares the loyalty of customers towards two major Indian telecom providers, Airtel and Jio. Despite both companies holding a substantial market share, they adopt distinct business models, marketing strategies, and customer service approaches that shape consumer loyalty in different ways. Through a combination of quantitative and qualitative research methods, including surveys, interviews, and a review of existing market data, this study investigates key factors influencing customer loyalty—such as network quality, pricing structures, brand image, customer support, and service innovation. The comparative analysis highlights that customer loyalty is not solely influenced by pricing or service availability but is deeply intertwined with emotional connections, trust, and perceived value. The study concludes that both Airtel and Jio have built strong customer bases, but their loyalty drivers differ significantly, and understanding these nuances can help both companies refine their strategies to enhance consumer retention.